Quantification of diabetic macular ischemia: Assessing agreement and reproducibility between Optical coherence tomography angiography and Fluorescein angiography - jeniffer trenado; sergio rojas juárez (Indonesian Vitreoretinal Society, 2020)
Introduction: The purpose was to assess the level of agreement and reproducibility between fluorescein angiography (FA) and optical coherence tomography angiography (OCTA), throughout the evaluation of the foveal avascular zone (FAZ) to diagnose diabetic macular ischemia (DMI). Methods: In this ambispective, observational, cross-sectional research, 41 patients underwent traditional FA and OCTA to obtain the level of agreement and reproducibility between them, using an intraclass correlation coefficient (ICC) in mixed models. Two raters independently graded the area of the FAZ using the ImageJ software and the Early Treatment Diabetic Retinopathy Study protocols. Spearman and rank-biserial correlational analysis were used to calculate the strength of linear relationship between the area of the retinal vessels, the thickness of subfoveal retinal and choroid layers, the presence of neovascularization, and the visual acuity. A classification, based on the radius of the FAZ, was proposed and used to categorize the severity of DMI into five different grades. Result: From 52 evaluated eyes, the level of agreement between the OCTA and FA among the raters had an ICC of 0.99 and 0.907 (p<.001), respectively. Furthermore, the reproducibility analysis had an ICC of 0.85 (p<.001). In the correlation analysis, the enlargement of the FAZ was associated with a decrease in the outer retinal layers (r=-0.458, p<0.001), the photoreceptor layer (r=-0.32, p=0.021), their outer segments (r=-0.32, p=0.021) and the subfoveal choroidal thickness (r=-0.483, p<0.001). A reduction of the vascular area was observed in higher grades of diabetic retinopathy (r= -0.395, p=0.38). Additionally, meager choroidal thickness was found in grater grades of DMI (r=-0.461, p=0.014). Conclusion: Compelling evidence of a high level of agreement and reproducibility between OCTA and FA was obtained to diagnose diabetic macular ischemia. Moreover, it is suggested that the increase in macular ischemia leads to the thinning of the photoreceptor, outer retinal and choroid layers.